Metronidazole versus lactic acid for treating bacterial vaginosis (VITA): protocol for a randomised controlled trial to assess the clinical and cost effectiveness of topical lactic acid gel for treating second and subsequent episodes of bacterial vaginosis - Armstrong-Buisseret, Lindsay; Brittain, Clare; David, Miruna; Dean, Gillian; Griffiths, Frances; Hepburn, Trish; Jackson, Louise; Kai, Joe; Montgomery, Alan; Roberts, Tracy; Thandi, Sukhwinder; Ross, Jonathan D. C. (My University, 2019)
Background Bacterial vaginosis (BV) affects 30-50% of women at some time in their lives and is an embarrassing and distressing condition which can be associated with potentially serious comorbidities. Current antibiotic treatments such as metronidazole are effective but can result in side effects, and recurrence is common. This trial aims to investigate whether lactic acid gel is clinically effective and cost effective in the treatment of recurrent BV compared with metronidazole. Methods VITA is an open-label, multicentre, parallel group randomised controlled trial for women with a clinical diagnosis of BV and at least one previous BV episode in the past 2 years. Participants will be randomised 1:1 to intravaginal lactic acid gel 5 ml once daily for 7 days or oral metronidazole tablets 400 mg twice daily for 7 days. All participants will be followed up for 6 months to assess health status and healthcare costs. A subgroup will be interviewed to further explore adherence, tolerability and acceptability of treatment. The estimated sample size is 1900 participants to detect a 6% absolute increase in response rate to 86% in those receiving lactic acid gel. The primary outcome is participant-reported resolution of BV at Week 2. Discussion Results from this trial will help inform UK treatment guidelines for BV and may provide an alternative effective treatment for recurrent episodes of this condition which avoids repeated exposure to antibiotics.
Keywords: Bacterial vaginosis; Lactic acid gel; Metronidazole; Recurrence; VITA; Antibiotic usage; Cost-benefit analysis